Value relevance of liabilities and non-performing loans in emerging market: IFRS adoption in Nigeria - Muhammad, Yusuf Alkali; Lode, Nor Asma (American Scientific Publishers, 2015)
This study uses a modified equity valuation model (stock price model) to examine the value relevance of balance sheet components (total liabilities (tl), deposit customer liability (dcl) and non-performing loans (npl)) for the periods before and during transition to IFRS in the Nigerian stock Exchange (NSE) Market.A 5-year data of 15 banks listed in the Nigerian stock market is selected as sample for the study.Using stock price model, the tl, dcl and npl measures were transformed into natural log (ln) form to arrive at a compatible and normal data.The results of the model provide evidence that accounting information is value relevant among Nigerian Banks.This is proved from the coefficient of tl and npl that negative but significant in the two periods of NGAAP and IFRS. In contrast, dcl provides a positive but also significant result under the two periods.The result further proves that IFRS is more value relevant than NGAAP. Lastly, we provide evidence from the R2 that there is greater association between accounting information and stock prices during the transition period (IFRS).Besides the significant of findings of this research to security market, the literature is providing contribution to limited market research in African capital market among banks, particularly in Nigeria after the IFRS adoption.